Implementasi Teknik Steganografi Menggunakan Algoritma Cardan Grille - Sartika Lumbangaol (Journal of Informatics, Electrical and Electronics Engineering, 2022)
Data security and confidentiality is an activity that aims to secure data, especially data that is confidential and important. If there is a break-in and theft of information of an important data in a file, it will be detrimental to the parties concerned. Therefore it takes Steganography technique is a technique that can hide messages or confidential information into other messages so that other people are not aware of the existence of the message to be hidden. In this study, the authors build a text data security system using the Cardan Grille Algorithm. whose main function is to hide messages, not to encrypt messages, so Cardan Grille is more often used for steganography. To do Cardan Grille, you need a perforated sheet and in the holes will be filled with letters, which are filled with letters, which are filled with messages and after that the sheet will be lifted and filled with the remaining sentences.